Rancang Bangun Media Pembelajaran Interaktif pada Mata Pelajaran Teknik Audio Video di SMKN 5 Padang - Ardiansyah, Ardiansyah; Efrizon, Efrizon (Lembaga Yasin AlSys, 2025)
The advancement of digital technology necessitates learning innovations in vocational high schools (SMK) to help students understand subject matter more effectively. Observations in Class XI TAV at SMKN 5 Padang revealed that instruction remains dominated by conventional methods, causing students to experience difficulties in learning, particularly with technical materials. This study aims to design and develop an interactive learning medium based on Smart Apps Creator for the subject of Programming and Microcontroller Applications. The method employed was Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The final product was an offline interactive learning application. Validation results indicated total scores of 0.846 from subject matter experts and 0.929 from media experts, both falling into the high-validity category. A practicality test involving 15 students yielded a percentage of 91.33% (highly practical). These findings confirm that the developed learning medium possesses high validity and practicality, making it feasible for implementation as a digital tool to enhance students’ understanding and engagement.